2008
DOI: 10.1103/physrevb.78.054301
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dynamics in the thermodynamic limit

Abstract: The description of spontaneous symmetry breaking that underlies the connection between classically ordered objects in the thermodynamic limit and their individual quantum mechanical building blocks is one of the cornerstones of modern condensed matter theory and has found applications in many different areas of physics. The theory of spontaneous symmetry breaking however, is inherently an equilibrium theory, which does not address the dynamics of quantum systems in the thermodynamic limit. Here, we will use th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(77 citation statements)
references
References 47 publications
1
76
0
Order By: Relevance
“…The mechanism of spontaneous symmetry breaking is traditionally formulated in an equilibrium description, thereby pre-empting any possibility of finding a state that does not obey the unitary symmetry. We have recently shown that this is not a necessary constraint, and that it is possible to give a dynamical description of spontaneous symmetry breaking in quantum mechanics which does indeed allow even the time translation symmetry to break down [5,6]. The time evolution resulting from the spontaneous breakdown of unitarity turns out to be surprisingly familiar: it reproduces precisely the quantum state reduction process observed whenever we try to measure a quantum state with an effectively classical measuring apparatus.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The mechanism of spontaneous symmetry breaking is traditionally formulated in an equilibrium description, thereby pre-empting any possibility of finding a state that does not obey the unitary symmetry. We have recently shown that this is not a necessary constraint, and that it is possible to give a dynamical description of spontaneous symmetry breaking in quantum mechanics which does indeed allow even the time translation symmetry to break down [5,6]. The time evolution resulting from the spontaneous breakdown of unitarity turns out to be surprisingly familiar: it reproduces precisely the quantum state reduction process observed whenever we try to measure a quantum state with an effectively classical measuring apparatus.…”
Section: Introductionmentioning
confidence: 84%
“…If the non-unitary field is a given, static field, it will always favour the component of a superposed wavefunction that is closest to its centre. Even if the location of that centre changes from one run of the experiment to another, this could never lead to a distribution of experimental outcomes that is correlated to the weight of individual components in the initial wavefunction [5,6,28]. However, we saw in the previous section that the conflict between general covariance and quantum mechanics can give rise to a non-unitary perturbation of Schrödinger's equation that is best modelled by the introduction of a time dependent stochastic variable, as in equation (16).…”
Section: Born's Rulementioning
confidence: 99%
See 1 more Smart Citation
“…The work of van Wezel (2007van Wezel ( , 2008van Wezel ( , 2010, which was brought to our attention only after the first version of this paper appeared on the arXiv, analyzes the spontaneous breakdown of continuous symmetries in a way compatible with (and indeed predating) our treatment the discrete case, including the fundamental observation about the instability of the symmetric ground state of a finite system under 'infinitesimal' asymmetric perturbations. Van Wezel (2010) also discusses the connection between ssb and the measurement problem, though his proposed solution to this problem is quite different from ours.…”
Section: Discussionmentioning
confidence: 99%
“…This works because in these models (in which the energy spectrum is discrete for any N < ∞), as N → ∞, on the one hand all energy levels merge into a continuum, but on the other, they split into pairs whose energy difference is exponentially small. In addition, the instability of the ground state has been derived in a different way by Narnhofer & Thirring (1996, 1999 for Z2, as well as by van Wezel (2007van Wezel ( , 2008van Wezel ( , 2010 for SU (2).…”
Section: First Excited Statesmentioning
confidence: 99%